If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -31 = 38 + 9x Reorder the terms: -31 + 12x = 38 + 9x Solving -31 + 12x = 38 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -31 + 12x + -9x = 38 + 9x + -9x Combine like terms: 12x + -9x = 3x -31 + 3x = 38 + 9x + -9x Combine like terms: 9x + -9x = 0 -31 + 3x = 38 + 0 -31 + 3x = 38 Add '31' to each side of the equation. -31 + 31 + 3x = 38 + 31 Combine like terms: -31 + 31 = 0 0 + 3x = 38 + 31 3x = 38 + 31 Combine like terms: 38 + 31 = 69 3x = 69 Divide each side by '3'. x = 23 Simplifying x = 23
| 5x+3=-x+21 | | 2x(4x-7)= | | 8+p=9 | | -x-17=11-2x | | 3-v+3=1-4v+1 | | -66+x=9x+62 | | 16x+21=46-y | | -7=-7x-3(-x+17) | | G=7F+6 | | -34-8x=29-11x | | 79x^2-200x+125=0 | | x+7+3x=13+x | | 6(a-3)= | | 45-33x+33-44x=-45+33x-33+44x | | 11x-11=7x+12 | | 4j+4=6 | | 6y-5=3+4y | | 3x^2y^4+7x^2y^4-10x^4y^2= | | 3k+5-k=-9 | | -2x=160 | | 2((x-2)/2)=0 | | 2((x-2)/2) | | 45-33x+33-44=-45+33x-33+44x | | 3y-3=14 | | -7x-3+6x=-8x+9 | | 12x+18y=50 | | -10x+10x-10x= | | 7a+5(a-3)= | | 35=3(5+2x) | | 2/3s-1/3=s/6=5/3 | | d-2.8/.2=-14 | | -16+5n=-7(-6+8n)3 |